INVESTIGATION OF NATURAL INHIBITORY ACTIVITY OF BLOOD SERUM IN ACUTE LEUKEMIA PATIENTS - G. M. Chernousova; N. К. Rodosskaya (Медицинская иммунология, 2014)
Abstract. The article contains results of studying the natural inhibitory serum activity in the patients with acute leukemia. A correlation is revealed between a resistance to myelosuppressive therapy, and positive inhibitory reaction towards immunoglobulins M. Determination of IL-2, IL-4 levels, as well as sulfhydril (SH- ) groups and amounts of blast cells at initial stage of disease are of high importance for early diagnosis of drug resistance upon the disease onset.